2023
DOI: 10.22201/iingen.0718378xe.2023.16.1.82387
|View full text |Cite
|
Sign up to set email alerts
|

Ação De Fungos Na Remoção De Metais De Águas Residuárias E Compartimentos Ambientais: Uma Revisão

Abstract: Os efluentes ricos em metais são muito comuns e geram grande preocupação, pois, embora estes elementos sejam encontrados facilmente na natureza, eles encontram-se em concentrações muito pequenas. Assim, a partir das ações antrópicas, os metais acabam sendo dispostos em ambientes onde não seriam facialmente encontrados e em concentrações elevadas, de modo que é necessário que esses poluentes sejam tratados de forma adequada e sustentável. Existem diversos métodos para remoção de metais, sendo eles químicos, fís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…For Ni 2+ , none of the isotherm models adequately fit the data, indicating that other interaction between the metallic ion and the biomass may happen, such as complexation. It may occur due to the complexation sites of the microbial biomass, which interact to form chelating complexes or gels containing organic structures like chitin (Magalhães et al, 2023;Sheikh et al, 2021). The FTIR analysis could preview these results since the IDBF after the retention of Ni 2+ showed minimal differences, suggesting the possibility of other removal mechanisms rather than biosorption and bonding to the IDFB activated sites.…”
Section: Biosorption Isothermmentioning
confidence: 98%
“…For Ni 2+ , none of the isotherm models adequately fit the data, indicating that other interaction between the metallic ion and the biomass may happen, such as complexation. It may occur due to the complexation sites of the microbial biomass, which interact to form chelating complexes or gels containing organic structures like chitin (Magalhães et al, 2023;Sheikh et al, 2021). The FTIR analysis could preview these results since the IDBF after the retention of Ni 2+ showed minimal differences, suggesting the possibility of other removal mechanisms rather than biosorption and bonding to the IDFB activated sites.…”
Section: Biosorption Isothermmentioning
confidence: 98%